The Growth of the Red Lactus (Lactuca sativa L. var. Crispa) After Using Nano Technology Liquid Organic Fertilizer Hydroponically cultivated - Nia Faradila; Resti Fevria; Vauzia Vauzia; Irma Leilani Eka Putri (Jurnal Biologi Tropis, 2023)
Hydroponics is a method of agriculture in which earth is not used. Among the plants amenable to hydroponic cultivation is red lettuce. One disadvantage of hydroponic cultivation is the occurrence of nutrient deposition, particularly in the wick system, where the nutrient water does not move. A technique that can lessen the amount of nutrient deposition that occurs in hydroponic systems is required in light of the aforementioned issues. Nanotechnology is one of the technologies developed. The five treatments and four replications in this study were P1 = AB Mix 100 percent, P2 = AB Mix 75 percent + POC Nano 25 percent, P3 = AB Mix 50 percent + POC Nano 50 percent, P4 = AB Mix 25 percent + POC Nano 75 percent, and P5 = POC Nano 100 percent. ANOVA (Analysis of Variance) was used to analyze the data, and the Duncan's New Multiple Range Test (DMRT) test at level 5 followed. The effects of nanotechnology-enhanced liquid organic fertilizer on red lettuce growth, including height, leaf area, number of leaves, fresh weight, and dry weight, were examined. The highest average plant is at P3 with a plant height of 36.42 cm, the highest average number of leaves is at P3 as many as 11.25 strands, the widest average leaf is at P4 with an area of ​​40.25 cm2, the average weight The highest wet weight was P4 with a weight of 17.01 g, and the highest average dry weight was P2 with a weight of 1.32 g.